Health-Related Quality of Life Before and After Use of a Smartphone App for Adolescents and Young Adults With Cancer: Pre-Post Interventional Study - Pappot, Helle; Assam Taarnhøj, Gry; Elsbernd, Abbey; Hjerming, Maiken; Hanghøj, Signe; Jensen, Marc; Boisen, Kirsten Arntz (JMIR Publications, 2019)
BackgroundAdolescent and young adult (AYA) patients with cancer are a group with underexplored needs throughout treatment and in survivorship. This missing knowledge can influence their quality of life (QoL). Given this fact, we have developed a smartphone app based on a cocreation process and have an investigation of QoL among users planned as part of pilot testing this app. Future research is warranted to determine the effect of mobile health (mHealth) tools such as smartphone apps among the AYA cancer population. ObjectiveThe aim of this study was to investigate the feasibility of a smartphone app among AYA patients with cancer in active treatment and posttreatment, in a pilot test by measuring health-related QoL before and after the use of the app. MethodsParticipants were recruited via the youth support initiative and social organization for AYAs with cancer, Kræftværket, based at Rigshospitalet, University Hospital of Copenhagen, Denmark. Participants were evenly distributed in active treatment and posttreatment groups. After written informed consent, all participants were asked to use the app Kræftværket as they deemed appropriate over a 6-week period. The participants were asked to complete the 30-item European Organization for Research and Treatment of Cancer Quality of Life Questionnaire before and after the 6-week period. The collected QoL data were analyzed with t tests to determine differences between groups and from baseline. ResultsIn total, we enrolled 20 participants, 10 in active treatment and 10 posttreatment (median time after treatment was 4 months) group. Median age of the participants was 25 years. No differences in QoL were seen at baseline (P=.65). The posttreatment group experienced a significant increase in overall QoL after the 6-week period (global QoL: baseline 62.5, SD 22.3; after 6 weeks 80.8, SD 9.7; P=.04). For the group in active treatment, the QoL remained stable throughout the 6 weeks. ConclusionsThis study shows the feasibility and possible effect on QoL associated with the use of an mHealth tool in AYA patients. mHealth support tools are warranted for this population.